Toxicidad aguda del extracto etanólico de Hymenaea oblongifolia huber (azúcar huayo) en ratones albinos cepa Balb C - Leon Flores, Yessenia Valeria (2025)
The medicinal resources of the Amazon forest are a natural encyclopedia known to locals; This knowledge hopes to achieve recognition in the scientific world. Objective: Determine the acute toxicity of the ethanolic extract of Hymenaea oblongifolia Huber (sugar huayo) in albino mice strain Balb C. Methodology: The correlational and experimental study assessed clinical, biochemical and anatomical histological parameters in the biological model at doses of 25 and 200 mg/kg. Results: The mortality rate at the dose of 25 mg/kg m.c. It was on average 13.33% and at the dose of 200 mg/kg it was 40.0%. In the animals that survived, loss of body mass was determined and in the parenchymal organs and the heart, vascular alteration and tissue damage were observed at the highest dose, detailed in decreasing order in the lungs > kidneys > brain = liver > heart. The average values of the biochemical parameters were almost all within the range of the normal values reported for their closest rodent and the values found for the control group. Conclusions: The evaluation of acute toxicity to the cortex organ of the species Hymenaea oblongifolia Huber (huayo sugar) of ethnomedicinal interest showed that it is harmful or highly dangerous.